Evaluation of a Mobile SMS based Twitter Information Service for Rural communities: A Case study of Ipologama Vidatha Resource Center, Sri Lanka - Ranhotige Madhavi Sandhyalekha Wijerathna; Uvasara Dissanayake; Sapna Navaratne; Darshana Gunawardena (Journal of the Community Development in Asia (JCDA), 2020)
Mobile phones have been effectively used to fulfill the information needs of rural communities in different contexts. This study was aimed to assess the effectiveness of a mobile-based twitter information dissemination service implemented by the Vidatha Resource Center, Ipologama, Sri Lanka applying the Technology Acceptance Model. Fifty-six respondents who have been using the service were selected for the study. Data were collected through an interview schedule. According to the results, the service was useful, easy to use and cost-effective depicting the potential use of such systems to fulfill the information needs of the rural communities.